Compliance Analysis of Nurses in Implementing Fall Risk Prevention in Post-Op Patients in the Jepun Room of Bali Mandara Hospital: A Case Study - Faridatul Khasanah; Kholid Rosyidi Muhammad Nur; Yulia Kurniawati; Ni Made Arik Mulyanti (KHD Production, 2024)
Falling risk is an increased sensitivity to falling that can result in physical injury and health problems. Nurses play a crucial role in reducing the risk of falls among patients in hospitals; therefore, nurses must adhere to established fall prevention protocols. The aim of this study is to assess nurses' compliance in implementing fall prevention measures for post-operative patients in the Jepun Room of Bali Mandara Regional General Hospital. The research design used is descriptive analysis in the form of a case study, with the study population consisting of 3 nurses from the Jepun Room at Bali Mandara Regional General Hospital. This study observes nurses' compliance in implementing fall risk prevention measures for patients. Based on observations, it was found that the implementation of mild fall risk prevention measures by 3 responsible nurses achieved 100% compliance. Specifically, ensuring non-slip footwear was applied 100% on the first day, with the lowest application being 0% on day 2 and 3. Meanwhile, measures such as providing patient orientation, obtaining patient consent to keep night lights on, and ensuring walking aids are within reach (if used) were never implemented, also at 0%. Regarding moderate fall risk prevention measures by these nurses, it was found that implementation was 100%. However, the installation of fall risk signs outside patient rooms had 0% implementation. From these findings, the role of these nurses as care coordinators in implementing fall risk prevention measures for patients is crucial to prevent undesired incidents.